GLOBAL SOLAR RADIATION ESTIMATION IN INDONESIA USING RADIAL BASIS FUNCTION NETWORK (RBF) WITH MULTIVARIABLE INPUT MTSAT DATA - SURENDRA (NIM : 22412306); Pembimbing : Dr. Nurjanna Joko Trilaksono, OKY
Research on solar radiation estimation has been conducted in order to overcome the limitations of the data. However, there is no research that produces a good surface solar radiation estimation for the entire territory of Indonesia, wich has varying characteristic of region and climat. So we purposed the new techniques to estimate the global surface radiation with better performance in spatially and temporally. In this study, a model of radial basis function (RBF) is used to estimate surface solar radiation throughout Indonesia, with multivariable input MTSAT data andthe value of top atmospheric radiation. The best model to estimate surface solar radiation according to experiments with 23 combinations input is: a model with input of all channels MTSAT and the value of top atmospheric radiation. Surface solar radiation data in this study was obtained from nine meteorological station for seven months, and MTSAT data was obtained from the Global Information System Center (GISC) Tokyo Portal. The validation from 10 different locations shown that RBFN performed very well. As the spatial and temporal perspective, this purposed methods gave a good accuracy and can represented the impact of interaction between topography with surface solar radiation, which is plateau/mountain region have lower solar radiation.